Real-time analysis of heart rate variability during aerobic exercise in patients with cardiovascular disease. (December 2022) - Ikura, Hidehiko; Katsumata, Yoshinori; Seki, Yuta; Ryuzaki, Toshinobu; Shiraishi, Yasuyuki; Miura, Kotaro; Sato, Kazuki; Fukuda, Keiichi
Abstract: Background: Exercise therapy for cardiovascular disease (CVD) is mainly evaluated based on the heart rate (HR) or Borg scale. However, these indices can be unreliable depending on the patient's medication or their subjective decisions; thus, alternative methods are required for easier and safer implementation of aerobic exercise. Here, we examined whether real-time analysis of HR variability (HRV) can help maintain exercise intensity at the ventilatory threshold (VT) during exercise. Methods: Twenty-eight patients with CVD treated at Keio University Hospital between August 2018 and March 2020 were enrolled. Initially, oxygen uptake (VO2 ) and HR at the VT were determined using the cardiopulmonary exercise test. Patients then performed aerobic exercise on a stationary bicycle for 30 min while a parameter of HRV, the high-frequency (HF) component, was monitored in real time using an electrocardiograph. The work rate during exercise was adjusted every 2 min to maintain the HF range between 5 and 10. The VO2 and HR values, recorded every 2 min during exercise, were compared with those at VT. The Bland–Altman method was used to confirm similarity. Results: VO2 and HR during exercise were closely correlated with those at VT (e.g., 19 min after exercise initiation; VO2 : r = 0.647, HR: r = 0.534). The Bland–Altman plot revealed no bias between the mean values (e.g., 19 min; VO2 : −0.22 mL/kg/min; HR: −0.07/min). Conclusion: Real-time HRV analysis with electrocardiograph alone during exercise can provide continuous and non-invasive exercise intensity measurements at VT, promoting safer and effective exercise strategies.